2013
DOI: 10.1007/s00464-013-2805-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term outcomes between laparoscopic greater curvature plication and laparoscopic sleeve gastrectomy

Abstract: The short-term outcomes of our study demonstrate that compared with LSG, LGCP is inferior as a restrictive procedure for weight loss, despite its significantly smaller cost. Longer follow-up and prospective comparative trials are needed to confirm the long-term outcomes of this novel procedure and make definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 23 publications
6
35
0
5
Order By: Relevance
“…19 Different studies had shown marked improvement in the preoperative co-morbidities following stomach plication technique. 9,17 In the present study improvement in co-morbidities was evident in 7 patients of 13 patients (53.8%). The improvement was more in those complaining of hypertension (3/4) and those who have joint pains (3/6) and lastly those having type II diabetes (1/3).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…19 Different studies had shown marked improvement in the preoperative co-morbidities following stomach plication technique. 9,17 In the present study improvement in co-morbidities was evident in 7 patients of 13 patients (53.8%). The improvement was more in those complaining of hypertension (3/4) and those who have joint pains (3/6) and lastly those having type II diabetes (1/3).…”
Section: Discussionsupporting
confidence: 58%
“…Another explanation of failure to lose weight sufficiently was due to insufficient lowering of Ghrelin hormone release from the gastric fundus. 17 The hospital stay in the present study was 3.3±1.6 days (3-5 days) and patients started oral feeding on 2 nd day.…”
Section: Discussionmentioning
confidence: 58%
“…Some authors prefer 2 rows of running sutures, some used 2 rows of interrupted sutures and others recommend a combination of running and interrupted sutures. 3,7,8,10,11,16,17,20,21 Inner layer sutures are better to be taken in an interrupted manner to adjust the plication and to avoid suture breaking of continuous layer leading to failure. The outer layer should be running stitch to avoid herniation in between.…”
Section: Resultsmentioning
confidence: 99%
“…10 Another prospective non-randomized study concluded that LGP is inferior to LSG as a restrictive procedure for weight loss, despite its significantly smaller cost at short term. 11 This lack of enthusiasm in LGP could be due to three main reasons which are:…”
Section: Introductionmentioning
confidence: 99%
“…[16] Shen et al have reported success rates lower than that of sleeve gastrectomy at the early stage. [17] El-Geider et al have published the 4-bit technique recommended by Talebpour and described a firm plication technique defining a 4-needle passage at each suture, which begins 2 cm below the His angle. [18] When compared to sleeve gastrectomy, the decrease in restrictive effect and weight re-gain are higher in the longterm.…”
Section: Discussionmentioning
confidence: 99%